El programa filosófico-político de Rousseau: el vínculo teórico entre el Discurso sobre los orígenes y fundamentos de la desigualdad entre los hombres y El contrato social - Gallo-Gómez, Juan Camilo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2021)
Este artículo busca presentar el legado teórico-político de Rousseau a través de la interpretación de su Discurso sobre los orígenes y fundamentos de la desigualdad entre los hombres y el Contrato social, entendidos como una unidad argumentativa y metodológica en la obra del ginebrino. Para esto se expondrán en un primer momento las consideraciones normativas y antropológicas que marcan el problema político de Rousseau. A partir de allí se presentarán las ideas principales de su noción de democracia, para finalmente concluir que el legado democrático de Rousseau resulta particularmente útil como elemento crítico en el contexto de la hegemonía de las democracias representativas liberales actuales.

“Rousseau’s Philosophical-political Program: the Theoretical Link between the Discourse on the Origins and Foundations of the Inequality Among Mankind and the Social Contract”. This paper presents Rousseau’s political and theoretical legacy through the interpretation of his Discourse on the Origins and Foundations of the Inequality Among Mankind and the Social Contract, understanding both as a sole argumentative and methodological unit in his work. In order to achieve this objective, the paper explores first the normative and anthropological considerations that mark the problem of Rousseau’s political theory. From there, the main ideas of his notion of democracy will be presented. Finally, the paper concludes that Rousseau’s democratic legacy is particularly useful as a form of critique in the hegemonic context of the current liberal and representative democracies.
Rousseau’s Philosophical-political Program: the Theoretical Link between the Discourse on the Origins and Foundations of the Inequality Among Mankind and the Social Contract
Keywords: Rousseau; Democracia; Igualdad; Libertad; Deliberación; https://purl.org/pe-repo/ocde/ford#6.03.01